2021
DOI: 10.3390/nano11102638
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Focusing and Vortex Generator Based on Polarization-Insensitive Gallium Nitride Metasurface

Abstract: In this paper, two polarization-insensitive Gallium Nitride (GaN) metasurfaces based on a dynamic phase for adjusting the wavefront are proposed. Specifically, we obtained the target phase to satisfy some design conditions by changing the structural parameters at the nanoscales. Under the irradiation of linearly polarized (LP) light and circularly polarized (CP) light, respectively, one of the metasurfaces can generate a focused beam with an efficiency of 84.7%, and the other can generate a vortex beam with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] In particular, these types of resonances become prominent when the meta-atom is either made of a high refractive index material or its size is comparable to the free space wavelength of light. [5] Recently, a variety of high-index materials including germanium, [17][18][19] gallium nitride, [20][21][22][23] silicon, [24][25][26] and titanium dioxide [27][28][29] has been used to explore various radiating and non-radiating states within metaatoms consisting of a single or a cluster of subwavelength particles of different geometries and configurations, such as trimer, quadrumer, and hexamer. [30][31][32] In addition to the studies of resonant excitations of individual meta-atoms, twodimensional periodic arrangements of these subwavelength particles, called metasurfaces, have been also shown to facilitate many exotic phenomena and applications, including beam steering, [33][34][35] actively controlled scattering patterns, [36][37][38] holography, [39][40][41] nonlinear harmonic generation, [42][43][44][45] Kerker, anti-Kerker, and transverse Kerker effects.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] In particular, these types of resonances become prominent when the meta-atom is either made of a high refractive index material or its size is comparable to the free space wavelength of light. [5] Recently, a variety of high-index materials including germanium, [17][18][19] gallium nitride, [20][21][22][23] silicon, [24][25][26] and titanium dioxide [27][28][29] has been used to explore various radiating and non-radiating states within metaatoms consisting of a single or a cluster of subwavelength particles of different geometries and configurations, such as trimer, quadrumer, and hexamer. [30][31][32] In addition to the studies of resonant excitations of individual meta-atoms, twodimensional periodic arrangements of these subwavelength particles, called metasurfaces, have been also shown to facilitate many exotic phenomena and applications, including beam steering, [33][34][35] actively controlled scattering patterns, [36][37][38] holography, [39][40][41] nonlinear harmonic generation, [42][43][44][45] Kerker, anti-Kerker, and transverse Kerker effects.…”
Section: Introductionmentioning
confidence: 99%
“…The above devices realize a propagating vortex beam rather than focused optical vortex (FOV), and the tightly FOV beam can form a gradient force to manipulate particles. Thus, the OV generator and lens can be integrated on a simple metasurface to produce FOV [32][33][34][35]. However, most of the work can only gain a single FOV with fixed topological charge, which will restrict the further tunable application of OV beam.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that due to the low diffraction limit, the vortex beam could replace the trivial Gaussian beam to improve the resolution of imaging, e.g., stimulated emission depletion, which can be of great use to biological and clinical medicine research [24]. Other recent applications in 2021 point to high-dimension OAMentanglement, and phase-gradient protection was also reported [25][26][27][28]. Many other exciting applications with regard to optical vortices are yet to be found.…”
Section: Introductionmentioning
confidence: 99%